Pengaruh Risiko Bisnis, Life Cycle Dan Diversifikasi Terhadap Struktur Modal Serta Hubungannya Dengan Nilai Perusahaan Manufaktur Di Indonesia - Septi Diana Sari (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2016)
This study aims to examine the factors that affect the capital structure. The task of the financial manager is to determine the amount of capital structure to enhance shareholder value. Since the capital structure associated with firm value , this study also aimed to examine the effect of capital structure on firm value by considering the company's diversification strategy and corporate life cycle stages . By using the data obtained from the OSIRIS period 2009-2012, researchers used multiple regression test and path analysis to test the hypothesis. From the test results stated that only companies which are in the start-up phase which has a significant positive effect on the capital structure , as well as the diversification strategy has an influence on the capital structure of the company's capital structure with a sequence of related diversification > unrelated diversification > single segment. But when regressed diversification strategy with corporate values, only a single segment strategy and related diversification which significantly affect the value of the company, as well as the positive effect of capital structure on firm value. Most of the results of this study can be explained by the signaling effect and the pecking order theory.